Service Learning in Cultural Heritage Preservation and Sustainable Tourism at Batu Caves, Kuala Lumpur, Malaysia - Satriadi Satriadi; Nur Asmah; Erdawati, Erdawati; Meilifia Liantifa; Ivan Ricardo; Aisha Dolisti Maulina (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This article discusses the application of service learning as an educational approach that supports the preservation of cultural heritage and the strengthening of sustainable tourism in Batu Caves, Kuala Lumpur, Malaysia. As one of the most important Hindu temple complexes in Southeast Asia, Batu Caves has become a symbol of cultural diversity and interreligious harmony. However, increased tourism activity has brought about various problems, such as environmental pollution, waste management issues, and the erosion of cultural values among visitors. To address these challenges, service-learning programs integrate academic theory with direct participation in the community, allowing students to actively engage in environmental conservation, cultural documentation, and the development of public education initiatives. Thru collaboration with temple managers, local communities, and tourists, students applied management concepts in real-world situations, including cleaning activities, maintaining tourist areas, developing educational materials on eco-tourism, and preserving traditional rituals thru cultural archiving. The implementation of this service learning not only enriches students' learning experiences but also raises public awareness about the importance of preserving Batu Caves as a sustainable cultural heritage site. Overall, this project demonstrates that service learning is a transformative pedagogical approach that connects academic goals with community development and cultivates future leaders who are socially responsible and culturally sensitive.